Majas Perbandingan dalam Novel 12 Cerita Glen Anggara Karya Luluk HF dan Implikasinya terhadap Pembelajaran Bahasa Indonesia - Lia Yuliana; Samosir, Astuti; Hilaliyah, Hilda (PT. Impola Toba Lendt, 2025)
Literature as an art form that uses language as its medium of expression, has complex and profound dimensions. One important aspect in literary works is the style of language, which not only reflects the author's skill in arranging words, but also has a significant influence on the reader's aesthetic experience and interpretation of the text. Authors often use several types of language styles in writing a novel, one of which is figurative language. The purpose of this study is to identify and analyze the use of comparative figures of speech in the novel 12 Stories of Glen Anggara by Luluk HF and its implications for Indonesian Language Learning. This study also aims to understand the types of figures of speech that contribute to strengthening the characters, plot, and themes of the story. The approach used in this study is a qualitative descriptive approach to describe the problem and focus of the research, by collecting literature in the form of articles published through books, scientific journals both printed and online. The instrument used is a classification table of findings of comparative figures of speech in the novel 12 Stories of Glen Anggara by Luluk HF. Based on the research results, 100 comparative figures of speech were found in this novel, including allegory, simile, personification, hyperbole, metaphor, depersonification, and eponym.